The Effectiveness of the Plus Tahfiz Programme in Strengthening Quran Memorisation and Its Impact on Students’ Academic Performance - Azarudin Bin Awang (Al-Bayān, 2025)
The memorisation of the Quran is a process of committing the verses of the holy Quran to memory, which not only strengthens religious knowledge but also serves as a foundation for creating a unique approach to learning. Due to its demanding nature requiring dedication and consistency, Quranic memorisation holds a special place in society. Among university students, Quran memorisers are perceived as notably active and popular compared to their peers. Therefore, this study was conducted to examine the effectiveness of Quranic memorisation retention through the Plus Tahfiz programme implemented by Universiti Teknologi MARA (UiTM). It also aims to identify the factors that motivate students to enrol in the Plus Tahfiz programme and to further explain the implications of the memorisation programme on students’ character development. This study employed a quantitative method with a population of 540 students and a sample of 256 students. Data were analysed descriptively using Structural Equation Modelling (SEM) in Smart PLS version 4.0.9.2. Five independent variables - Effectiveness, Empowerment, Support, Challenges, and Attitude - were tested against the dependent variable, Academic Influence (ACI). Results revealed that Support (t = 2.435) and Attitude (t = 3.673) had significant positive effects on ACI, whereas Effectiveness, Empowerment, and Challenges showed no statistically significant impact. The findings suggest that reinforcing Support and Attitude within the programme could enhance academic achievement, highlighting their critical role in student success.